PENGARUH LOKASI TERHADAP KEPUTUSAN MEMILIH JASA PENGIRIMAN BARANG PADA PT. TIKI JALUR NUGRAHA EKAKURIR (JNE Express) GRESIK - Farida, Nur (GEMA EKONOMI, 2018)
The purpose of this study is to know the influence of location to decision of choosing shipping service on PT. TIKI Jalur Nugraha Ekakurur (JNE Express) Gresik. This study is done in PT. TIKI Jalur Nugraha Ekakurur (JNE Express) Gresik., this study is explanatif with quantitative approach, sample is collected by sampling accidental technique with 90 respondents of sample data collected method that relates to the research question is done by using quistionnaire methode. The study result of 90 respondents show that the influence of service choosing decision based on regression calculation by using SPSS 18.00 for windows is resulted t value is 6,404 with p value is 0,000 by using significant limitation $=0,05 is resulted t table is 1,987 because of t value (6,404) > t table (1,987) thus variable location (X) influences significant on service choosing decission (Y). That result show that Ho rejected and H1 accepted. Thus it can be concluded that location has positive influences and significant on service choosing decision to PT. TIKI Jalur Nugraha Ekakurir (JNE Express) Gresik.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477645